Análise de superfície seletiva em frequência para sinais do padrão IEEE 802.11 - Soares, Danilo Luan de Almeida (Universidade Federal Rural do Semi-Árido, 2018)
In the present work, the dual-band frequency selective surface is proposed to filter signals in the IEEE 802.11 standard at 2.45 and 5.80 GHz. In this sense, the FSS with conductive patch was designed to behave as a filter rejects-track. With the objective of reducing the multiple paths, a resistive patch was designed to be applied in conjunction with the conductive. Results for the coefficient of transmission as a function of frequency were obtained using the Ansoft HFSS software, in this step, some changes were made via software to correspond to the real conditions, such as the addition of materials, where the FSS was supposedly applied, such as plasterboard, concrete and wood, are used to describe the cut-off frequency. The results obtained for the conductive surface prove the dual-band behavior and meet the industrial and scientific bandwidths (ISM).
Monografia
Keywords: Superfície Seletiva em Frequência; Dual-band; Wireless; CIENCIAS EXATAS E DA TERRA::CIENCIA E TECNOLOGIA